Impact of technologies assessed, refined, Demonstrated and Disseminated to Paddy farmers - a case study - Venkateshwar Rao, N; Jain, PK; Kishor Kumar, N; Reddy, M Jagan Mohan (Journal of Agricultural Extension Management, 2018)
The present paper highlights the level of knowledge and extent of adoption of paddy production technologies and the impact on productivity and profitability of farmers in Karimnagar district of Telangana State. Ex post facto research design was adopted and ninety farmers were selected for the study. A high level of knowledge, high extent of adoption and a minimum of ten percent increased productivity and profitability were observed among the farmers adopting the technologies as compared to the non-adopter farmers. A positive and significant correlation was observed with most of the profile characteristics of farmers adopting the technologies when compared to non-adopter farmers.